A comparative study on e-banking services between China and USA. (14th August 2009) - Yang, Jiaqin; Cheng, Li; Luo, Xia
This paper describes a comparative study about the issues in the current e-banking services among the young consumers between two nations: China vs. USA. As the attitude and usage of young consumers will be a good indicator for the trend of e-banking service in the future, and different cultures and traditions will play a role in the development of e-banking industry among different nations, this comparative study provides insightful guidelines for the development of e-banking industry in both nations and worldwide. Managerial implications are discussed with suggestions for future research.